Flora of Rio Grande do Norte, Brazil: Boraginales - Miranda De Melo, José Iranildo; Paulino, Renan Da Cruz; de Oliveira, Regina Célia; Vieira, Diego Daltro (Phytotaxa, 2018)
A taxonomic treatment of the Boraginales of Rio Grande do Norte, Brazil, is presented. Twenty-one species in five genera and two families have been recorded: Cordiaceae, with two genera (Cordia (seven species) and Varronia (four)) and Heliotropiaceae, with three genera (Euploca (five), Heliotropium (two) and Myriopus (three)). Cordia oncocalyx and Euploca paradoxa represents new occurrence records for the flora of Rio Grande do Norte, the latter being found for the first time also in the littoral vegetation. Keys to the families and respective genera and species, descriptions and illustrations, as well as distribution and habitat data are included.